Distribuição e Possível Origem de Metais Pesados nos Sedimentos de Fundo ao Longo da Bacia do Alto Rio Tietê: Aplicação da Normalização Geoquímica Sucessiva - Mortatti, Jefferson; de Moraes, Graziela Meneghel; Kiang, Chang Hung [UNESP] (My University, 2012)
Geochemical analyses of major heavy metals were conducted on vertical profiles of riverbed sediments from upper Tietê river basin to determine the possible elemental sources. The applied method involved a successive normalizing of the geochemical fractions related to organic and anthropogenic influences, carbonate or acid soluble and clastic mineral detritus. In the headwaters of upper Tietê River basin was verified an association with anthropogenic sources (atmospheric fallout and redox) mainly at uppermost part of sediments, while in depth, the metals showed to be related with the carbonate fraction. At Pirapora sampling station, after the anthropogenic influences of São Paulo city, most of heavy metals were associated to organic matter fraction, while Zn and Co showed anthropogenic characteristics, mainly related to domestic sewage and industrial effluents.
Origin and distribution of heavy metals in bottom sediments along the river basin high Tietê: Geochemical aspects of standardization successive
Keywords: Bottom sediment; Geochemical; Heavy metal; Upper Tietê river basin